Study oon myco-coagulsnt from lentinus squarrosulus for water turbidity reduction - Hamidah Hassan (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
Water treatment of river water for human consumption involved the use of chemical coagulant to reduce suspended solids and turbidity. However, chemical coagulant has negative impacts thus research is carried out for bio-coagulant alternatives. In this research, basidiomycete fungi (Lentinus squarrosulus strain 7-4-2), which was named as RWF, was used as a source of secondary metabolites which have the potential in water treatment due to the flocculating ability. Laboratory experiments were conducted to optimize the production of the extracellular polymeric substance from Lentinus squarrosulus. Physical and environmental conditions important for the growth of RWF were selected using Plackett-Burman design (PBD). Physicochemical parameters such as concentration of yeast extract (1%), malt extract (1%) and NaCl (1%); as well as the initial pH (5), culture temperature (35 °C), agitation speed (250 rpm), culture period (8 days) and inoculum size (4%) were selected based on PBD, which resulted in turbidity reduction of synthetic waste water from kaolin solution up to 88 % inside 250 ml shake flask. Agitation speed and yeast extract have been identified as the main effects. The raw coagulant could reduce the turbidity from 460 NTU to 83 NTU, resulting in a reduction of about 82% in the next experiment. The myco-coagulant produced from the optimized growth condition was used to further purify the final product using cross flow filtration. After crossflow filtration using 30 kD membrane, the supernatant produce retentate and filtrate with turbidity reduction of 84% and 70%, respectively. It can be concluded that both the retentate and filtrate had good flocculation ability, although the retentate showed 14% more ability compared to the filtrate; indicating that the larger sizes of proteins were more efficient in reducing the turbidity, compared to the proteins smaller than 30 kD size. Use of various sizes of cross flow filters would help narrow down the most efficient size of the coagulant produced by the fungus RWF (Lentinus squarrosulus strain 7-4-2).